Socialization of Occupational Health and Safety (K3) for Workers Construction on Bridge Projects - Asri Afriliany Surbakti; Dasrizal; Mei Brilian; Alif Saum Rizalitaher; Ibnu Signori; Wahyu Widodo (PT FORMOSA CENDEKIA GLOBAL, 2023)
Construction is hard work which involves many elements, from the use of heavy equipment to the involvement of large amounts of materials. This causes the world of construction to have a higher risk of work accidents compared to other types of work. For this reason, all parties must understand the importance of implementing Occupational Safety and Health (K3) in construction projects. Socialization of the application of K3 was carried out including the bridge project on Jalan Bilal, Medan. The service will be held on January 16 2023 at 11.00 – 13.00 WIB with the lecture and discussion method. In the early stages, the speaker gave a lecture by introducing the types of personal protective equipment and the importance of applying K3. Then a discussion was held, where the presenter gave the opportunity to the participants to ask questions about K3. In-depth knowledge of OSH and awareness of workers to implement OSH is the result to be achieved in this service